Ayat Amtsal Al-Qur’an sebagai Media Terapi Wicara untuk Anak Disleksia: Pendekatan Melodi, Makna, dan Multisensorik - Maslachah, Maslachah; Satiadharmanto, Deddi Fasmadhy (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Dyslexia is a specific learning disorder affecting reading skills, especially phonological awareness and language processing. Multisensory speech therapy based on Amthal (Quranic parables) offers rhythmic stimulation, symbolic meaning, and cultural contexts that can enhance neuroplasticity and reading abilities in children with dyslexia. Objectives: This study aims to explore the potential of Amthal verses as a speech therapy medium that integrates melody, symbolic meaning, and multisensory stimulation to improve reading skills and brain activation in children with dyslexia. Methods: A qualitative literature review was conducted, synthesizing scientific and theoretical sources related to neurocognition, neuroplasticity, and multisensory speech therapy to identify mechanisms of Amthal use in therapy. Results: Findings indicate that Amthal verses contain rhythmic linguistic patterns enhancing phonological awareness through superior temporal gyrus activation; culturally meaningful contexts strengthen emotional engagement via cortisol reduction and ventral striatum activation; and visual metaphors support semantic processing via fusiform gyrus and hippocampus integration. Conclusion: Quranic Amthal verses serve as an effective therapeutic medium within multisensory speech therapy for dyslexic children, offering holistic neurocognitive and cultural benefits. This approach is promising as an evidence-based intervention in the Indonesian context. Keywords: Amthal, Dyslexia, Multisensory speech therapy, Neuroplasticity, Local culture